EFEKTIVITAS GAYA KEPEMIMPINAN KEPALA DESA DALAM PEMBANGUNAN INFRASTRUKTUR DI KECAMATAN CIMANUK, PANDEGLANG - Amir, Firman; Wulandari, Florentina Ratih; Afandi, Muhamad Nur; Anggraini, Katry (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2025)
The study aims to analyze the effectiveness of the Village Head’s leadership style in infrastructure development in Cimanuk District, Pandeglang Regency, Banten Province. Using a qualitative approach supported by quantitative data, the research collected information through surveys, in-depth interviews, and document analysis. The findings indicate that participative and situational leadership styles are more effective in increasing community engagement compared to the instructive (directing) style. Additionally, this approach accelerates the implementation of infrastructure development. Key factors determining the success of development include transparency in budget management, two-way communication, strengthening coordination systems between village officials and the community, and active community involvement in village programs. These findings highlight that adaptive and inclusive leadership can enhance the effectiveness of infrastructure development. As a recommendation, village governments should strengthen leadership capacity by prioritizing participation and transparency to ensure more inclusive and sustainable development. This is expected to improve overall community welfare and accelerate the achievement of village development goals effectively.